Kalam Nahy dalam al-Qur’an: Kajian Balaghah terhadap Makna Ḥaqiqiy dan Majaziy: Kalām Nahy in the Qur'an: a Balāghah Study of The Meanings of Ḥaqīqiy and Majāziy - Rina Fauziah Jufri; Mohamad Harjum; Muh. Fihris Khalik (STAI Ma'had Aly Al-Hikam Malang, 2026)
Kalam nahy is a form of prohibitive expression in Arabic that plays a significant role in the study of balaghah, particularly in understanding the meanings and rhetorical purposes of Qur’anic verses. This article aims to examine kalam nahy in the Qur’an from a balaghah perspective, focusing on its haqiqi and majazi meanings. This study employs a library research method with a descriptive-analytical approach to classical works of balaghah and relevant Qur’anic verses. The findings reveal that kalam nahy in the Qur’an functions not only as a legal prohibition but also serves rhetorical purposes such as warning, advice, emphasis, reproach, and other expressive meanings. Therefore, understanding both haqiqi and majazi meanings of kalam nahy is essential for a more comprehensive and contextual interpretation of the Qur’an